Changing natures: a perspective on youth and conservation futures - Jagadeesh, Shruthi N. (Frontiers in Human Dynamics, 2024)
Conservation has been a largely exclusionary and exploitative process that has its roots in western colonial expansion. This paper offers a perspective on the relationship between the conservation apparatus and young adults who live in/depend on Protected Areas and have grown up within a strict conservation regime. Following Feminist Political Ecology's call to better understand the situated and heterogenous relationships to nature within communities, I bring attention to the lives of Soliga tribal youth in a Tiger Reserve in South India. I challenge mainstream perceptions that youth inevitably want to leave their forest homes, arguing that the difficult choices youth must make today, are informed by decades of life under restrictive laws that alienate communities from the forest over generations. Young people's lives and aspirations are contradictory and nuanced, and their relationships to the forest remain strong and should not be discounted. This research addresses a significant gap in the literature, and my data illustrates the need to include the experiences of youth as a central tenet of unfolding dialogues on inclusive and decolonial approaches to conservation.